2022
DOI: 10.1101/2022.12.16.22283582
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of Olfactory Dysfunction with the Omicron Variant of SARS-CoV-2: A Systematic Review and Meta-analysis

Abstract: The omicron variant is thought to cause less olfactory dysfunction than previous variants of SARS-CoV-2, but the reported prevalence differs greatly between populations and studies. Our systematic review and meta-analysis provide information about regional differences in prevalence as well as an estimate of the global prevalence of olfactory dysfunction based on 41 studies reporting on nearly 600,000 patients infected with the omicron variant. Our estimate of the omicron-induced prevalence of olfactory dysfunc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 134 publications
0
5
0
Order By: Relevance
“…As a result, a large majority of survey-reported SCIs in the validation set were associated with COVID-19 symptoms (92%). In contrast, a meta-analysis of Omicron infections estimated 32.4% of infections were asymptomatic (31). This may result in a slight upward bias in overall sensitivity estimates.…”
Section: Discussionmentioning
confidence: 94%
“…As a result, a large majority of survey-reported SCIs in the validation set were associated with COVID-19 symptoms (92%). In contrast, a meta-analysis of Omicron infections estimated 32.4% of infections were asymptomatic (31). This may result in a slight upward bias in overall sensitivity estimates.…”
Section: Discussionmentioning
confidence: 94%
“…The lower prevalence of olfactory and taste disorders among Omicron-infected individuals when compared to other previous variants has been reported previously [ [28] , [29] , [30] , [31] , [32] , [33] ]. A recent meta-analysis including 62 studies and 626,035 patients reported that olfactory disturbances caused by Omicron are about 2–10 times less common than observed with the Alpha or Delta variants [ 34 ]. Features associated with the mechanism of Omicron entry into the host cell may explain, at least in part, a lower efficiency in infecting olfactory epithelial cells [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were demonstrated by the REal-time Assessment of Community Transmission (REACT-1) study, which reported subjective symptoms from 1,542,510 randomly selected participants in England from 1.5.20 to 31.3.22 (121) . A recent systematic review and meta-analysis of OD in patients infected with the omicron variant demonstrated a global prevalence of 3.7% (122) . However, this varied geographically, with higher rates seen in people of European ancestry (11.7%).…”
Section: Prevalence and Clinical Presentationmentioning
confidence: 99%